WHICH PROCESSES OF PRIVATE INSTITUTIONS FOR TERTIARY EDUCATION DESERVE A KEY FIGURE? - Stefan, Friedrich (European Scientific Journal, ESJ, 2014)
The sector of private educational institutions in Austria is very young but crowing. Despite the urgent necessity of customized and directly applicable control mechanisms there are still little knowledge and experience due to the recentness of the sector. Controlling in educational institutions has rarely been explored to this day. Up until now only the sub-areas of controlling of educational processes have been researched. Institutions which are dealing with working students have to offer special service in terms of opening hours, service quality, lectures etc. which causes higher costs and requests a high budget liability. In order to develop a customized controlling instrument for educational institutions in higher education an examination of the crucial influencing factors of private educational institutions is necessary. In further consequence, parameters, measuring criteria and key figures can be developed on this basis to create customized controlling. Aim of the following part is an intensive examination of the processes of private educational institutions. This will be used as a basis for a further evaluation of processes in order to determine the influence of particular processes in educational institutions. To reach this aim the necessary and trendsetting processes will be defined with regard to the exemplary institutions Ingenium Education and Studienzentrum Weiz.